A decade of Marcellus Shale: Impacts to people, policy, and culture from 2008 to 2018 in the Greater Mid-Atlantic region of the United States. Issue 4 (November 2018) - Jacquet, Jeffrey B.; Junod, Anne N.; Bugden, Dylan; Wildermuth, Grace; Fergen, Joshua T.; Jalbert, Kirk; Rahm, Brian; Hagley, Paige; Brasier, Kathryn J.; Schafft, Kai; Glenna, Leland; Kelsey, Timothy; et al.
Highlights: Approximately 15, 939 wells have been drilled and fracked at 5674 sites, producing more than 41, 675, 025 MMcf of natural gas and billions of barrels of gas and oil liquids. This decennial documents the pace, scale, and stages of actual development and takes stock of the social science on impacts to communities, people, policies, and culture. We detail the size and distribution of multi-well pad development across the Mid-Atlantic. We examine the perceived impacts to residents in Ohio amid complex historical natural resource lineages. We conclude with a discussion of research opportunities and directions as a new generation of social scientists document future development in the Marcellus and Utica Shales. Abstract: It's been just over a decade since Unconventional Oil and Gas development began in earnest in the Marcellus Shale, a dense shale formation that, along with the deeper and larger Utica Shale, covers much of the mid-Atlantic United States. Since January 2008, approximately 15, 939 wells have been drilled and fracked at 5674 sites across these shales. This decennial documents the pace, scale, and stages of actual development and takes stock of the social science on impacts to communities, people, policies, and culture. We have divided this article into the following sections that are categorized both geographically and thematically: Pennsylvania: Heart of the Marcellus Shale Play, focuses on the plethora of social science research that has occurred on impacts to Pennsylvania communities, health, economics, and agricultural production; West Virginia and Ohio: Legacies of Extraction discusses research on the overlapping historical legacies of extractive industries in the region and details results of original research examining perceived impacts to residents amid complex historical natural resource lineages; and New York: Fracking, Culture and Politics examines how the regulatory process to develop the Marcellus Shale affected both the state and nation's culture, politics, and policy as one of the most densely populated regions of the US came to grips with hosting the modern-day Oil and Gas Industry. We conclude with a discussion of emerging research opportunities and directions as a new generation of social scientists document future development in the Marcellus and Utica Shales.